Morphological and semantic aspects of deonomical verbs in the German language - Ziyadullaev, Ilhom (The Lingua Spectrum, 2025)
The present article investigates the morphological and semantic characteristics of deonominal verb neologisms in the German language that originate from anthroponyms, primarily the names of political and public figures. Such lexical innovations as “merkeln, scholzen, seehofern, guttenbergen, hartzen, trumpisieren, and orbánisieren” represent a productive process of linguistic creativity whereby proper names are transformed into verbs. From a morphological perspective, these units are predominantly formed through the German verb-forming suffix -en or the international suffix -isieren, reflecting different degrees of lexical integration and stylistic markedness. Semantically, they function as stereotypical metonymies that condense socially recognized patterns of behavior, political strategies, or personal traits into a single linguistic unit. Pragmatically, such verbs serve as discourse tools that allow speakers and writers to express evaluative, often ironic or critical, stances in political communication and mass media. The study demonstrates that anthroponymic verb neologisms are not marginal phenomena but dynamic elements of the German lexicon, which highlight the close interrelation between language, politics, and culture.